Six2 Plays an Intrinsic Role in Regulating Proliferation of Mesenchymal Cells in the Developing Palate - Okello, Dennis O.; Iyyanar, Paul P. R.; Kulyk, William M.; Smith, Tara M.; Lozanoff, Scott; Ji, Shaoping; Nazarali, Adil J. (Frontiers in Physiology, 2017)
Cleft palate is a common congenital abnormality that results from defective secondary palate (SP) formation. The Sine oculis-related homeobox 2 (Six2) gene has been linked to abnormalities of craniofacial and kidney development. Our current study examined, for the first time, the specific role of Six2 in embryonic mouse SP development. Six2 mRNA and protein expression were identified in the palatal shelves from embryonic days (E)12.5 to E15.5, with peak levels during early stages of palatal shelf outgrowth. Immunohistochemical staining (IHC) showed that Six2 protein is abundant throughout the mesenchyme in the oral half of each palatal shelf, whereas there is a pronounced decline in Six2 expression by mesenchyme cells in the nasal half of the palatal shelf by stages E14.5–15.5. An opposite pattern was observed in the surface epithelium of the palatal shelf. Six2 expression was prominent at all stages in the epithelial cell layer located on the nasal side of each palatal shelf but absent from the epithelium located on the oral side of the palatal shelf. Six2 is a putative downstream target of transcription factor Hoxa2 and we previously demonstrated that Hoxa2 plays an intrinsic role in embryonic palate formation. We therefore investigated whether Six2 expression was altered in the developing SP of Hoxa2 null mice. Reverse transcriptase PCR and Western blot analyses revealed that Six2 mRNA and protein levels were upregulated in Hoxa2−/− palatal shelves at stages E12.5–14.5. Moreover, the domain of Six2 protein expression in the palatal mesenchyme of Hoxa2−/− embryos was expanded to include the entire nasal half of the palatal shelf in addition to the oral half. The palatal shelves of Hoxa2−/− embryos displayed a higher density of proliferating, Ki-67 positive palatal mesenchyme cells, as well as a higher density of Six2/Ki-67 double-positive cells. Furthermore, Hoxa2−/− palatal mesenchyme cells in culture displayed both increased proliferation and elevated Cyclin D1 expression relative to wild-type cultures. Conversely, siRNA-mediated Six2 knockdown restored proliferation and Cyclin D1 expression in Hoxa2−/− palatal mesenchyme cultures to near wild-type levels. Our findings demonstrate that Six2 functions downstream of Hoxa2 as a positive regulator of mesenchymal cell proliferation during SP development.